1)0.9
2)а.-5/14
б.-5/21
в.1/6
3).-2
4)
а)-14/15
б)-1.11/16
в)7/30
Пошаговое объяснение:
-3/10× - 3=0.9 уможаем знаменатели (-3= -3/1)
5/4*(-2/7) = -10/28 =-5/14
-3/7 *5/9 =сократим 3 и 9. -1/7 * 5/3=-5/21
-4/9 * -3/8 =сократим 4 и 8, 9 и 3= 2/3 *1/4= 2/12=1/6
14/3* -3/4× 4/5÷(-5/6)×6/7=(- 14/1*1/4)×(-2/5÷5/3)*6/7=(- 7/2) * (-2/3) *6/7= -7/3*6/7=-6/3=-2
а)2/3÷(-5/7)=умножаем на дродь обратную
2*7/3*-5= -14/15
-3/4÷4/9=-3*9/4*4 =-27/16=-1 11/16
-7/15÷(-2)=7/30
1)0.9
2)а.-5/14
б.-5/21
в.1/6
3).-2
4)
а)-14/15
б)-1.11/16
в)7/30
Пошаговое объяснение:
-3/10× - 3=0.9 уможаем знаменатели (-3= -3/1)
5/4*(-2/7) = -10/28 =-5/14
-3/7 *5/9 =сократим 3 и 9. -1/7 * 5/3=-5/21
-4/9 * -3/8 =сократим 4 и 8, 9 и 3= 2/3 *1/4= 2/12=1/6
14/3* -3/4× 4/5÷(-5/6)×6/7=(- 14/1*1/4)×(-2/5÷5/3)*6/7=(- 7/2) * (-2/3) *6/7= -7/3*6/7=-6/3=-2
а)2/3÷(-5/7)=умножаем на дродь обратную
2*7/3*-5= -14/15
-3/4÷4/9=-3*9/4*4 =-27/16=-1 11/16
-7/15÷(-2)=7/30